Association between parental, peer, and teacher attachment, and cyberbullying - Kiatrungrit, Komsan (Journal of the Psychiatric Association of Thailand, 2021)
Objective: To study association between parent, peer, and teacher attachment, and cyberbullying. Method: This is a cross–sectional descriptive research in 1,144 Mattayomsuksa 1–3 students in Bangkok. The research tools were personal information questionnaires, cyberbullying questionnaires, and attachment to parents, peers (inventory of parental attachment and peer attachment-Revised; IPPA-R) and teachers questionnaires (Inventory of teacher-student relationships; IT-SR). Descriptive statistics were used to find frequency, percent, and mean. Analytic statistics such as chi-square, anova, and multinomial logistic regression were employed to find the association. Result: The study showed that more than half of the students have experienced cyberbullying (56.7%). They were divided into three groups in following order 1) victims group (25.2%), 2) both victims and cyberbullies group (24.4%), and bullies group (7.2%). Male, low average family income, social media usage and Instagram usage were found to be related with previously bullies group. The victims and bullies group were found to be related with male, Mattayom 1 students, time spent on internet for more than 7 hours/day, not using internet to find information, and weak attachment to parents and friends. The victims group were found to be related with Mattayom 1 students, time spent on internet for more than 7 hours/day, not using internet to find information and weak attachment to parents, but strong attachment to teachers. Discussion: Many of students had experiences about cyberbullying in various ways such as being victims, bulliers, or both. Various factors were found to be associatated with these experiences. Individual factors which found to be associated with cyberbullying are sex and level of education. Moreover, internet usage such as time spent on and kind of media use were also found to be associated with these experiences. One important protective factor which found in this is attachment, whether it be parent or peer attachments. They were found associated with decrease in cyberbullying experiences. Despite teacher attachment was found to be associated with increase in being cyberbullying victim, it might be explained by teacher who have good relationship with the victims can be their counsellors. Conclusion: According to the study, parents and teachers should be encouraged to establish good relationships with children through communication, build trust, and reduce alienation. In addition, building good social skill in children is important to make them have good relationship with friends and prevent cyberbullying.